Tamoxifen Effects on the lipid profile in premenopausal women with Breast cancer: A follow up study - Ali, Zainab A. M.; Jasim, Wasan K.; Hussein, Dilan Z.; Alnaqash,Manwar Abd. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Breast cancer composed of several biologic subtypes that have response to hormonal therapy. Tamoxifen is hormonal therapy with tissue- pecific antagonistic or agonist effects, the latter being responsible for multiple effects on lipid metabolism in women . Objective: This study was designed to determine the impact of Tamoxifen on the serum lipid profile in breast cancer women. Patients and methods: Prospective observation cohort study conducted at Oncology Teaching Hospital, Medical city complx.starting from October 2015 to October 2016. A total number of 40 premenopausal women with breast cancer were enrolled in this study according to inclusion criteria . Patients were followed for three months by the measurements TC, TG, HDL – cholesterol and BMI . Results: At the end of third months of hormonal therapy, Tamoxifen showed a significant decrease in TG, VLDL (p< 0.001 for both). On the other side HDL and BMI showed significant increase over three months duration , (p = 0.001 and 0.006, respectively) . Conclusion: Beneficial alterations of lipid profiles were seen in pre-menopausal breast cancer patients treated with Tamoxifen.